The importance of project management: A case study of KLIA Premier Holdings Sendirian Berhad - Ahmad, Hartini; Mohtar, Shahimi; Romli, Azizi; Ramli, Azhari; Hassan, Mohamad Ghozali (Universiti Utara Malaysia, 2013)
The Chairman/CEO of KLIA Premier Holdings Sendirian Berhad, Tan Sri Dato’ Dr. Ir. Jamilus bin Hussein was discussed with his personal assistance on the schedule for the 2nd week in November 2010 at the office in Bandar Baru Bangi, Selangor.It was at 8.35am in the morning and he made a final checked on the agenda for the company meeting with all the General Managers of the subsidiaries at 10.00am today.He needs to get all the updates on the performances of the subsidiaries in the group of companies. His concern was on the issue of incremental cost for the projects at Low Cost Carrier Terminal that still pending for handover to client Malaysia Airport Berhad.For example, inconsistency in material prices may, if not carefully planned and forecasted, may result in a delay, higher cost or even a failure of a project.Even this morning while in the car going to the office, he had a lot of thoughts on the plan to enhance the company business for competitiveness in order to continue leveraging on domestic opportunities and to compete in the global market.As he said, The vision is to be the leading provider and the household name in all the avenues that the group had ventured. This we will achieve by delivering quality and cost effective services to all our clients globally and we will lead the way in using the state of the art technology to achieve the above in an innovative as well as environmental friendly manner.We are an equal opportunity organization and we provide equal opportunities to our employees with maximum professional development and optimum rewards.Our stakeholders will be rest assured of expecting fair returns.